2016
DOI: 10.1007/s00410-016-1254-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic evaluation of the Zr-in-rutile thermometer in ultra-high temperature (UHT) rocks

Abstract: different steps of the metamorphic evolution. Rutile grains that equilibrated their Zr concentrations at temperatures above 1070 °C (i.e. 1.1 wt% Zr) could not retain all Zr in the rutile structure during cooling and exsolved baddeleyite (ZrO 2 ). By subsequent reaction of baddeleyite exsolution lamellae with SiO 2 , zircon needles formed before the system finally closed at 650-700 °C without significant net loss of Zr from the whole host rutile grain. By reintegration of zircon exsolution needles, peak metamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 41 publications
(87 reference statements)
4
81
3
Order By: Relevance
“…Zircon exsolution has been observed in nature (e.g., Ewing et al, 2013;Pape et al, 2016) and has been demonstrated experimentally with Zr-rich rutile (Tomkins et al, 2007). Resulting zircon appears as thin exsolution lamellae or as small individual euhedral grains within rutile.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…Zircon exsolution has been observed in nature (e.g., Ewing et al, 2013;Pape et al, 2016) and has been demonstrated experimentally with Zr-rich rutile (Tomkins et al, 2007). Resulting zircon appears as thin exsolution lamellae or as small individual euhedral grains within rutile.…”
mentioning
confidence: 89%
“…Metamorphic precipitation of zircon could be a result of the breakdown of and/or exsolution from various Zr-bearing phases (Davidson and van Breemen, 1988) such as garnet, amphibole, (clino)pyroxene and ilmenite (e.g., Fraser et al, 1997;Degeling et al, 2001;Möller et al, 2003;Söderlund et al, 2004;Harley et al, 2007;Kelsey et al, 2008;Morisset and Scoates, 2008), hemo-ilmenite (Morisset et al, 2005), baddeleyite (Bingen et al, 2001;Söderlund et al, 2004), rutile (Harley et al, 2007;Tomkins et al, 2007;Morisset and Scoates, 2008;Kelsey and Powell, 2011;Ewing et al, 2013Ewing et al, , 2014Pape et al, 2016), epidote, titanite (Kohn et al, 2015), chlorite (Fraser et al, 2004), and biotite (Vavra et al, 1996). Zircon coronae have been reported around Martian baddeleyite as a result of shock metamorphism (Moser et al, 2013).…”
Section: Zr-bearing Phases Potentially Associated With Zircon Precipimentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of fluids, metamorphic zircon may form via solid-state (partial) recrystallisation (e.g. Schaltegger et al 1999;Hoskin and Black 2000;Tomaschek et al 2003;Rubatto et al 2006) or by the breakdown of Zr-rich minerals (Fraser et al 1997;Degeling et al 2001;Bingen et al 2004;Ewing et al 2013;Pape et al 2016). …”
Section: Introductionmentioning
confidence: 99%